Ilececum: A Comprehensive Review - Shou-jiang Tang; Ruonan Wu (Canadian Journal of Gastroenterology and Hepatology)
For gastrointestinal endoscopists, the ileocecum is the finishing line during colonoscopy and it is identified by three endoscopic landmarks: terminal ileum, ileocecal valve, and the appendiceal orifice. Although ileal intubation is recommended during routine screening colonoscopy, it is not required in most cases of screening colonoscopy. Ileal intubation is indicated in certain circumstances such as suspected inflammatory bowel disease and GI bleeding. There is much pathology that can be observed within the ileocecum. Careful and systematic examination should be stressed during GI endoscopic training and practice. In this review, the authors demonstrate its anatomy, endoscopic findings, and pathologies.